Synthesis of von Willebrand Factor by Cultured Human Endothelial Cells - Jaffe, Eric A. (1974)
Cultured human endothelial cells synthesize and secrete a protein(s) which has Factor VIII antigen but which lacks Factor VIII clot-promoting activity (J. Clin. Invest. 52, 2757-2764, 1973). Von Willebrand factor activity has been identified in medium from cultured human endothelial cells. This activity was demonstrated by the ability to correct the defect in platelet adhesiveness of blood obtained from patients with von Willebrand's disease. This activity also supported ristocetin-induced aggregation of washed normal human platelets. The von Willebrand factor activity from cultured endothelial cells has physicochemical and immunologic properties like those of the von Willebrand factor activity and the Factor VIII antigen present in human plasma and the Factor VIII antigen synthesized by human endothelial cells in vitro. Rabbit antibody to chromatographic fractions containing endothelial cell von Willebrand factor inhibits the platelet retention of normal blood in glass bead columns.